Resistance to progressive collapse of monolithic frames of buildings at localized damage of nodes from push-through - A. V. Alekseytsev; M. D. Antonov (Vestnik MGSU)
Introduction. When designing buildings and structures it is necessary to ensure mechanical safety throughout the life cycle of the object. During the operation of buildings, situations arise in which monolithic load-bearing structures acquire defects in the area of the slab-column connection (SCC) in girderless slabs. These are, first of all, cracks caused by bending of slabs and slab pushing through by columns. The problem of taking into account the operation of structures with regard to such data of local damages in emergency situations is not sufficiently studied. In a number of cases the loss of bearing capacity of nodes is of brittle nature, which is not allowed by normative documents, as it can lead to progressive, including avalanche-like, destruction of neighboring elements.Materials and methods. The bearing capacity of elements and the degree of resistance to progressive failure of a 9-storey monolithic girderless frame under different scenarios of initial local damages are determined. Three levels of such damage are introduced, and the slab and column connection nodes are modeled by volumetric finite elements. Verification of the computational model is performed experimentally by in-situ pushover tests of the SCC under central load application. Simulia Abaqus software package is used for the purpose of calculations. The CDP model is used for modelling of concrete deformations, and bilinear diagrams with hardening are used for modelling of reinforcement deformations.Results. Experimental data on the deformations of the slab-column connection under longitudinal force loading and realization of the push-through mode are obtained. Taking into account the selected damage levels and experimental data, calculations of the monolithic frame with different damage scenarios in the investigated nodes are carried out. The nature of force redistribution for frames with different levels of such damage and the degree of their danger in the realization of progressive failure are established.Conclusions. It is determined that damages in the nodes of column and girderless slabs interfaces can lead to redistribution of forces and changes in the character of slab operation. These changes can initiate progressive failure in emergency situations in case of structural solutions of nodes with two-sided and three-sided design contours in terms of CP 63.13330 for push-through calculations. Additional design justification is required for such nodes.